Pengaruh Modal Usaha terhadap Pengembangan (UMKM) di CV. Kakarak Food - Putri Siti Maesyaroh; Faizal Hamzah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to analyze the influence of business capital on the development of Micro, Small, and Medium Enterprises (MSMEs) at CV Kakarak Food located at Jl. Gunung Batu No. 117T, Sukaraja, Cicendo, Bandung, West Java. This study uses a quantitative method with an associative descriptive approach. Primary data were obtained through distributing questionnaires to 30 respondents who are employees at CV Kakarak Food, while secondary data were obtained from company documentation and relevant literature. The data analysis technique used was simple linear regression to test the partial effect of the independent variables on the dependent variable. The results of this study indicate that venture capital has a positive and significant influence on the development of MSMEs. The availability of venture capital helps streamline operational activities, strengthen production capacity, improve product quality, and support business expansion efforts to a wider market. Furthermore, venture capital also contributes to increasing company competitiveness in facing the dynamics of the food industry. Therefore, it can be concluded that increasing venture capital is a crucial aspect that must be considered in encouraging the growth and sustainability of MSMEs, particularly CV Kakarak Food and similar MSMEs in the food sector. This research is expected to provide input for business owners, the government, and related parties in designing MSME development strategies oriented towards capital strengthening, thus creating more stable, independent, and highly competitive businesses in the future. Furthermore, the results of this study can also serve as an academic reference for further research and as evaluation material for MSMEs in determining managerial policy priorities.